“I didn’t know what to do, where to go”: The voices of students whose parents were born in Latin America on the need for care in Quebec universities - de Oliveira Soares, Roberta; Magnan, Marie-Odile (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
This qualitative study reports the university experiences of Quebec students whose parents were born in Latin America. The analysis, which looks at students who have either persisted in school or discontinued their studies, underscores the importance of cultural capital and, especially, an understanding of the student craft for school retention. The students report a low sense of affiliation with the university, and a perceived lack of support and care from the university and its social actors. Our interpretation of the data highlights self-blame for the challenges faced in university concurrently with the implementation of strategies to meet the challenges of the institution. We conclude by emphasizing how important it is for universities to support students better, adequately inform them about their options and the institution’s inner workings, and form a community with students in a spirit of care.